MASTER OF GUIDANCE AND COUNSELING EFFORTS TO INCREASE ADJUSTMENT STUDENTS SMA NEGERI 1 ANGKOLA TIMUR - Malim Saleh (Ristekdik : Jurnal Bimbingan dan Konseling, 2016)
The role and presence of guidance and counseling teachers in addressing low achievement in school is very important. It can be seen from the results of interviews and research conducted at SMA Negeri 1 Angkola Timur, with the title of Master of Guidance and Counseling efforts in dealing with the low learning achievement. The purpose of this study was to determine the extent of the problems experienced by students related to student achievement. In addition, this study also aims to how the role of guidance and counseling teachers in dealing with low student achievement.The population in this study were all students of SMAN 1 Angkola Timur and X-XII classes totaling 137 students. While the number of samples used as objects of this research are as many as four students as representatives of the population and plus 1 teacher guidance and counseling.The method used by the researchers in conducting this study is a qualitative method. To conclude the data and information on the problems studied, the researchers use interviewing techniques, documentation study and observation of spaciousness. Data and information obtained were developed and analyzed to determine the results and concluded.From these results it can be concluded that the guidance and counseling teacher has a very strong role in addressing the low learning achievement in SMAN 1 Angkola Timur. Therefore the guidance and counseling teacher is also required to be able to create a variety of appropriate measures to tackle and deal with the issue